Association of Serum YKL-40 Level with Tumor Burden and Metastatic Stage of Prostate Cancer - Enver Ozdemir; Tarık Cicek; Mehmet Onur Kaya (Urology Journal, 2012)
PURPOSE: To investigate the relationship between serum level of YKL-40 and Gleason score, grade and stage of the disease, and for the first time, with tumor burden in patients with prostate cancer (PCa). MATERIALS AND METHODS: Serum levels of YKL-40 and prostate-specific antigen were measured in 34 men (mean age: 66 years) with newly diagnosed and untreated PCa, in 34 men (mean age: 65 years) with biopsy proven benign prostatic hyperplasia, and in 29 healthy young men (mean age: 24 years). RESULTS: Serum YKL-40 concentration in men with PCa and benign prostatic hyperplasia, and in controls were 165.67 ± 107.84 ng/mL, 137.38 ± 82.04 ng/mL, and 69.69 ± 18.46 ng/mL, respectively. Serum level of YKL-40 was correlated with tumor burden in 30.4% of the patients with PCa (P = .04). A cut-off serum YKL-40 value of 92.696 ng/mL produced 70.6% sensitivity and 93.1% specificity. Elevated serum level of YKL-40 was strongly associated only with metastatic stage of the PCa. No association was observed between elevated level of YKL-40 and Gleason score groups or Gleason grade. CONCLUSION: Our results suggest that elevated serum level of YKL-40 may be a useful indicator of tumor burden and metastatic stage of PCa. Further studies are warranted to better elucidate the meaning of YKL-40 in tumor burden and invasiveness.